PRDM15 is a key regulator of metabolism critical to sustain B-cell lymphomagenesis - Mzoughi, Slim; Fong, Jia Yi; Papadopoli, David; Koh, Cheryl M.; Hulea, Laura; Pigini, Paolo; Di Tullio, Federico; Andreacchio, Giuseppe; Hoppe, Michal Marek; Wollmann, Heike; Low, Diana; Caldez, Matias J.; et al. (Nature communications, 2020)
PRDM (PRDI-BF1 and RIZ homology domain containing) family members are sequence-specific transcriptional regulators involved in cell identity and fate determination, often dysregulated in cancer. The PRDM15 gene is of particular interest, given its low expression in adult tissues and its overexpression in B-cell lymphomas. Despite its well characterized role in stem cell biology and during early development, the role of PRDM15 in cancer remains obscure. Herein, we demonstrate that while PRDM15 is largely dispensable for mouse adult somatic cell homeostasis in vivo, it plays a critical role in B-cell lymphomagenesis. Mechanistically, PRDM15 regulates a transcriptional program that sustains the activity of the PI3K/AKT/mTOR pathway and glycolysis in B-cell lymphomas. Abrogation of PRDM15 induces a metabolic crisis and selective death of lymphoma cells. Collectively, our data demonstrate that PRDM15 fuels the metabolic requirement of B-cell lymphomas and validate it as an attractive and previously unrecognized target in oncology. The transcriptional regulator PRDM15 is expressed at low levels in normal tissues but overexpressed in B-cell lymphomas. Here, the authors show that PRDM15 depletion does not affect adult somatic cell homeostasis but leads to a metabolic crisis which impairs B-cell lymphomagenesis.